A TRANSFORMATIONAL LEADERSHIP, REWARD, AND PUNISHMENT PHYSICAL WORK ENVIRONMENT AND ITS INFLUENCE ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE WORK MOTIVATION - Dimas Prayoga; Andini Nurwulandari (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study aims to find out the influences of determine consist of Transformational Leadership, Reward and Punishment, and Physical Work Environment on the Employee Work Motivation of the RGD, Corp. Then, this research analyzes the influence of Transformational Leadership, Reward and Punishment, and Physical Work Environment towards Employee Performance through Employee Work Motivation of the RGD, Corp. This type of research is associative with a quantitative approach. The amount of samples in this study is 100 respondents. The data analysis technique used a structural equation model (SEM). Transformational Leadership has a positive and non-significant influence on Employee Work Motivation and Employee Performance. Reward and Punishment have a positive and significant influence on Employee Work Motivation and Employee Performance. Physical Work Environment has a positive and significant influence on Employee Work Motivation, while has a negative on Employee Performance. Employee Work Motivation has a negative and significant influence on Employee Performance. Each Reward and Punishment, then the Physical Work Environment has a significant influence on Employee Performance through Employee Work Motivation, but Transformational Leadership has a negative and non-significant influence on the Employee Performance of RGD, Corp.Keywords: Reward and punishment, Physical work environment, employee work motivation, employee performance